Vpliv izbranih okoljskih dejavnikov na dinamiko vlaženja bukovine - Žlahtič Zupanc, Mojca (Acta silvae et ligni, 2016)
Beech is one of the most important tree species in Slovenia. Unfortunately, there is much more beech wood incremented annually than consumed. Thus, it is of great importance to develop new applications for use of beech wood. One of the possible solutions is use of beech in outdoor applications. However, if beech is used outdoor it has to be somehow protected. In the recent period, non-biocidal methods of wood protection such as thermal modification and use of wax emulsions are gaining more and more importance, hence we applied these two methods to beech wood in present research as well. During the research, water exclusion efficacy of wood was determined. Wood was subjected to various abiotic and biotic degradation protocols. The results exhibited that the best water performance was achieved in wax treated thermally modified beech. Water performance of wax treated wood was not affected by abiotic and biotic degradation factors. By contrast, the aging protocols applied considerably reduced water exclusion efficacy of beech and thermally modified beech wood.
Keywords: beech wood; bukovina; termična modifikacija; thermal modification; naravni voski; natural waxes; vlažnost lesa; wood moisture content; water uptake; navzem vode; odpornost; performance; water repellence